Women in Prison, 1800-1935: Tennessee, New York, and Ohio - Rafter, Nicole Hahn ([Verlag nicht ermittelbar], 1986)
This data collection focused on problems in the women's correctional system over a 135-year period. More specifically, it examined the origins and development of prisoner and sentencing characteristics in three states. Demographic data on female inmates cover age, race, parents' place of birth, prisoner's occupation, religion, and marital status. Other variables include correctional facilities, offenses, minimum and maximum sentences, prior commitments, method of release from prison, and presence of crime partners.